An Analysis of the Learning Difficulties of Class B Fifth-Semester Students of Arabic Language Education in Studying Arabic at Institut Agama Islam Hamzanwadi NW Lotim - Muhamad Hasyim; Muhammad; Muh. Rizwan Al-Azhari; Muhammad Jamiluddin; Muhammad Hafizullah; Lena Riska; Novika Dwi (Formad English Foundation NTB Jakarta, 2026)
This study aimed to analyze the learning difficulties experienced by Class B fifth-semester students of the Arabic Language Education Study Program at Institut Agama Islam Hamzanwadi NW Lotim in studying Arabic. The research specifically investigated the dominant factors causing students’ learning difficulties, explored students’ experiences during the Arabic learning process, and examined the pedagogical and environmental factors influencing Arabic language acquisition. This study employed a qualitative approach with a descriptive case study design. The participants consisted of fifth-semester students and lecturers of the Arabic Language Education Study Program selected through purposive sampling. Data were collected through classroom observation, semi-structured interviews, and documentation conducted from March 15 to April 20, 2026. The data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings revealed that students’ Arabic learning difficulties were influenced by interconnected linguistic, psychological, pedagogical, environmental, and institutional factors. Linguistic difficulties became the dominant barriers, particularly in vocabulary mastery, understanding of nahwu and sharaf, reading comprehension, and sentence construction. Psychological factors such as low motivation, language anxiety, and lack of self-confidence also significantly affected students’ participation and communicative competence. In addition, monotonous instructional methods, limited Arabic-speaking environments, insufficient technological integration, and unequal educational backgrounds contributed to students’ learning difficulties. The study concluded that improving Arabic language acquisition in Islamic higher education requires communicative and student-centered instructional approaches, supportive learning environments, institutional support, and effective integration of digital learning technologies.